Disiformasi dan Peran Pendidikan: Membangun Kesadaran di Kalangan Generasi Muda - Wahdini Rohmah Jaelani; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Jurnal Multidisiplin Indonesia, 2023)
The development of information and communication technology and globalization have given rise to cultural and civic literacy problems. One of the problems in cultural and civic literacy is the phenomenon of disinformation. The rise of disinformation is caused by the younger generation who are closely connected to social media. The young generation who were born and grew up with technology makes it easier for them to receive various information on social media. The information on social media is not entirely true. Therefore, there is a need for a solution to build awareness of the younger generation regarding the phenomenon of disinformation. The research method used is a literature study of articles related to the disinformation phenomenon. The results of this research are that education plays a role in building awareness of the younger generation. Efforts that can be made are to implement cultural and civic literacy in the school, family and community environment.